The Relationship Between Early Breastfeeding Initiation (IMD) and the Incidence of Uterine Involution in the Benao Community Health Center Work Area - Siti Morliana; Anik Sri Purwanti (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
Background: Early Breastfeeding Initiation (IMD) is the practice of allowing newborns to breastfeed within the first hour after birth. This practice is not only beneficial for establishing mother-infant bonding but also plays a crucial role in stimulating uterine contractions through the release of oxytocin, which can accelerate uterine involution in postpartum mothers. Uterine involution is an important physiological process that prevents postpartum hemorrhage and supports maternal recovery. Despite the known benefits, not all mothers practice IMD immediately after delivery, which may affect the process of uterine involution. Objective: This study aimed to analyze the relationship between Early Breastfeeding Initiation (IMD) and the incidence of uterine involution in postpartum mothers at the Benao Community Health Center Work Area. Methods: A quantitative, observational study with a cross-sectional design was conducted involving 30 postpartum mothers selected through purposive sampling. Data were collected on IMD practices and uterine involution assessments. The Wilcoxon signed-rank test was used to analyze the relationship between IMD and uterine involution. Results: The study found a significant relationship between IMD and uterine involution (p = 0.000). Mothers who practiced IMD within the first hour postpartum showed a faster and more effective uterine involution process compared to those who did not. Conclusion: Early Breastfeeding Initiation (IMD) is significantly associated with the incidence and speed of uterine involution in postpartum mothers. Promoting IMD immediately after birth is essential for supporting maternal recovery and preventing postpartum complications